论印尼本土汉语教师与中国志愿者教师的教学焦虑对比研究 - Phanata, Stephanie (Journal of Maobi, 2024)
Teaching anxiety is a problem that teachers feel deeply in teaching practice. Whether it is local Chinese teachers in Indonesia or Chinese volunteer teachers, they will feel anxious when teaching, coupled with the characteristics of students, different classroom teaching situations, language and cultural communication barriers, etc. In Chinese teaching, perhaps very simple knowledge for teachers, students have a lot of difficulties to learn, teachers will inevitably have a kind of anxiety, which will affect the smooth implementation of teaching work. When Chinese teachers face pressure, how to find the cause of teaching anxiety and take measures to overcome anxiety is of great significance to carry out teaching work. This article explores the teaching anxiety problems and performance comparisons of local Chinese teachers in Indonesia and Chinese volunteer teachers, promoting the physical and mental health development of teachers to improve teaching effectiveness.